2017
DOI: 10.18261/issn.1504-2936-2017-03-04-04
|View full text |Cite
|
Sign up to set email alerts
|

Klima for endring?

Abstract: SAMMENDRAGMenneskeskapte klimaendringer er en av vår tids store utfordringer, spesielt for landbruket som både er en betydelig bidragsyter og som kan bli hardt rammet gjennom endrede dyrkingsbetingelser. St.meld. nr. 39 (2008St.meld. nr. 39 ( -2009) Klimaendringene -landbruket en del av løsningen bygger på at landbruket skal ta sektoransvar for å bidra til å oppfylle norske klimamål. Dette fordrer driftsendringer og tilpasninger på bruksnivå, og bonden blir dermed en sentral aktør for klimapolitisk måloppnåels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A survey from the CSCAPE project on Norwegian farmers' relationship with global climate change and agricultural practises showed that 98 percent of Norwegian farmers had no plans to make specific investments or restructure their operations on the grounds of climate change (Aasprang 2013, Brobakk 2017). 1 Nevertheless, 41 percent expected to be affected by climate change within the next ten years; significantly, as many expected positive outcomes for their businesses as expected negative ones.…”
Section: Climate Policy and Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…A survey from the CSCAPE project on Norwegian farmers' relationship with global climate change and agricultural practises showed that 98 percent of Norwegian farmers had no plans to make specific investments or restructure their operations on the grounds of climate change (Aasprang 2013, Brobakk 2017). 1 Nevertheless, 41 percent expected to be affected by climate change within the next ten years; significantly, as many expected positive outcomes for their businesses as expected negative ones.…”
Section: Climate Policy and Agriculturementioning
confidence: 99%
“…One interpretation of the data is that farmers held only weak opinions about near-future interrelationships between everyday farming practises and climate change, and only a minority (42 percent) were engaged in the climate debate. When asked to rank policy priorities, issues related to farm economy and food production are more important than reducing GHG emissions from the farm sector (Brobakk, 2017). Hulme (2009) argues that the main reasons for disagreement about how to cope with climate change are connected to how we wish to live together in society.…”
Section: Climate Policy and Agriculturementioning
confidence: 99%